Correlation Between Neutrophil to Lymphocyte Ratio (NLR) and Procalcitonin Levels in Sepsis Pneumonia Patients - Purba, Angela Yurika; Bihar, Syamsul; Sinaga, Bintang Y.M. (CoinReads Media Prima, 2024)
Introduction: According to the World Health Organization's global health estimates, lower respiratory infections are the fourth leading global cause of deaths and the deadliest communicable disease, causative for three million deaths worldwide in 2016. Despite the introduction of antibiotic therapies in the 1950s, pneumonia mortality has not decreased substantially, and sepsis, septic shock or acute pulmonary failure (eg acute respiratory distress syndrome, ARDS) are frequent secondary complications. To improve management and treatment of pneumonia, supporting microbiological and virological tests from throat swabs, sputum or blood cultures might be indicated to identify the responsible pathogen(s) and to allow targeted antimicrobial or antiviral therapy. To determine the relationship between procalcitonin level and neutrophil to lymphocyte ratio in sepsis pneumonia patients. Method: This study was conducted with an observational analytic design conducted in a cross-sectional manner, from January 2023 to December 2023. The subjects of this study were taken from the population of sepsis pneumonia patients who were hospitalized at intensive care unit, were found to be 132 samples. Data included procalcitonin level and neutrophil to lymphocyte ratio from laboratory findings, were analyzed with univariate and bivariate method to assess the relationship between procalcitonin level and neutrophil to lymphocyte ratio. Results: In this study, white blood cell, neutrophil and neutrophil/lymphocyte ratio values were found to be significantly higher in patients with elevated procalcitonin. Among the 132 samples, the mean of procalcitonin level was between ≥ 2 to 10 (39,39%) and neutrophil to lymphocyte ratio was between ≥ 11 to 17 (50%). Conclusion: There was no significant relationship between procalcitonin level and neutrophil to lymphocyte ratio in sepsis pneumonia patient at intensive care unit in Adam Malik Hospital Medan (P value 0.816).